Environmental and anthropogenic factors affecting coastal bathing water quality : preliminary study for Primorje-Gorski Kotar County (Croatia) - Mance, Diana (Array, 2021)
Coastal bathing water, as a common good, is an economic resource of public health interest. Predictive models of coastal bathing water contamination are needed for timely prevention of pollution, warning of bathers, and activation of municipal services and utilities in case of contingencies, as well as institutional mechanism designs for common good management purposes. The goal of this research is to identify the variables that would improve predictive models of coastal bathing water bacterial contamination. The microbiological quality of coastal bathing water is affected by many variables. This research is an analysis of the following determinants: precipitation amount, seawater temperature and salinity, as well as few indicators of anthropogenic pressure on the environment such as registered population, registered tourist overnight stays and the amount of generated municipal waste, all possibly directly or indirectly affecting the bathing water quality in 17 coastal municipalities in the Primorje-Gorski Kotar County. The analysis showed that rainfall, as an instrumental confounder variable, influences salinity and seawater temperature by increasing groundwater discharge and bringing contamination i.e. increasing enterococci and Escherichia coli concentrations in coastal bathing water. Population as the conjectured independent variable, representing the anthropogenic cause of pollution, was once again falsified as a statistically significant determinant. For further research, longer-term sampling (preferably year-round) at micro-locations of comparable hydrogeological characteristics is recommended.